From the Shadows of Civilisation and Racist Ideologies Towards Post-assimilation - Keskitalo, Pigga; Sarivaara, Erika; Linkola, Inker-Anni; Paksuniemi, Merja (Palgrave Macmillan, 2018)
The Sámi people have gone through a long period of enlightenment project driven by church, and nationalistic assimilation aspirations in all the countries they live in – through hidden or more conscious processes. Basically, the ideologies behind these pursuits are based on white supremacy that the Sámi should have been civilized and put under national state societal organization. Due to rather destructive history of ideologies, there are Sámi generations who have lost at least partly their cultural and linguistic special features. This has weakened also their cultural identity to some extent. Hence, the history of Sámi reflects the current situation of the people. Sámi education’s purpose is to resolve a severe phenomenon in Sámi society whereby structural power has challenged everyday practices. Sámi Education searches for the practices based institutional education on Indigenous knowledge, traditions, and cultural context. Sámi Education is a means to resolve the legacy of assimilation and, in particular, language shift. Sámi Education that is based on a mediating role plays an important part in efforts to revive Indigenous languages and cultures. Aiming to gain wide access to education, health, economics, wellness, political representation, and other factors that are essential to leading a good life. The article goes beyond the shadows of colonial practices. The love, hope, and sharing is to resolve legacy of colonization. The article is based on research material gathered in two phases. Keywords: the Sámi people; assimilation; racism; Sámi education; mediating structures; anti-racist education The Sámi people have gone through a long period of enlightenment project driven by church, and nationalistic assimilation aspirations in all the countries they live in – through hidden or more conscious processes. Basically, the ideologies behind these pursuits are based on white supremacy that the Sámi should have been civilized and put under national state societal organization. Due to rather destructive history ...